Transformasi Sistem Pembelajaran Berbasis Teknologi untuk Mencetak Generasi Unggul - Ilahi, Dewi Shinta Kurnia; Muttaqien, Moh Hasan Firghol; Bukhori, Imam (Kartika: Jurnal Studi Keislaman, 2025)
The transformation of learning systems is a crucial component in shaping excellent generations capable of competing at the global level, particularly amid the dynamics of the Fourth Industrial Revolution and the demands of 21st-century education. This study aims to identify the driving factors behind changes in learning systems and analyze their impact on educational quality and students’ future readiness. Using a literature review method, this research explores the integration of educational technology, competency-based approaches, 21st-century skills curricula, and the evolving role of teachers. The findings indicate that technologies such as Learning Management Systems (LMS) and interactive learning applications enhance accessibility, active student participation, and the effectiveness of self-directed learning. Curricula emphasizing skills such as communication, collaboration, creativity, and problem-solving are deemed essential to meet the challenges of an increasingly complex professional world. Moreover, competency-based assessments and the shift in the teacher’s role to facilitator contribute significantly to creating an inclusive and flexible learning environment. Thus, learning system transformation serves as a critical foundation for building adaptive and sustainable education